Microbial precipitation of Cr(VI) during methane fermentation of environmentally hazardous plant Ambrosia artemisiifolia - Tymoshenko, A.D.; Kyrylov, S.K.; Bida, I.O.; Havryliuk, O.A.; Hovorukha, V.M.; Tashyriev, O.B. (Problems of Environmental Biotechnology, 2023)
Plants of the Ambrosia genus are invasive and cause many ecological problems, including the suppression of the growth of crops, and the production of strong allergens. Thus, the problem of hazardous weeds spreading entails serious economic and social consequences. Another ecological problem is the pollution of the environment by toxic metals, particularly soluble Cr(VI) compounds. Plant A. artemisiifolia can be used as a high-energy substrate for biomethane production and chromate detoxification simultaneously during its anaerobic degradation due to the reduction soluble CrO42– to insoluble Cr(OH)3nH2O↓. Herein, the work aimed to confirm experimentally the possibility of methanogenic degradation of A. artemisiifolia biomass and effective detoxification of toxic chromate.